2018
DOI: 10.4049/jimmunol.1800386
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl–Transfer RNA Synthetase Induces the Maturation of Dendritic Cells through MAPK and NF-κB Pathways, Strongly Contributing to Enhanced Th1 Cell Responses

Abstract: In addition to essential roles in protein synthesis, lysyl-tRNA synthetase (KRS) is secreted to trigger a proinflammatory function that induces macrophage activation and TNF-a secretion. KRS has been associated with autoimmune diseases such as polymyositis and dermatomyositis. In this study, we investigated the immunomodulatory effects of KRS on bone marrow-derived dendritic cells (DCs) of C57BL/6 mice and subsequent polarization of Th cells and analyzed the underlying mechanisms. KRS-treated DCs increased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Recent elegant work demonstrated that multiple mARS subunit components are differentially phosphorylated and dissociate from the complex in response to vesicular stomatitis virus (VSV) and influenzavirus infection. Once dissociated, these subunits bind and activate essential components of innate antiviral immunity, thereby implicating the mARS as both a sensor and regulator of the immune response to viral infection 68,69 . Canonically, the mARS complex is reported to possess only 8 of the 19 known mammalian aminoacyl‐tRNA synthetase isoforms (glutamyl‐prolyl, isoleucyl, leucyl, glutaminyl, methionyl, lysyl, arginyl, and aspartyl) 40,64,65,68 which, if true under all homeostatic conditions, could limit its utility as a sensor capable of discerning amino acid homology between epitopes not possessing one or more of the cognate amino acid residues.…”
Section: Resultsmentioning
confidence: 99%
“…Recent elegant work demonstrated that multiple mARS subunit components are differentially phosphorylated and dissociate from the complex in response to vesicular stomatitis virus (VSV) and influenzavirus infection. Once dissociated, these subunits bind and activate essential components of innate antiviral immunity, thereby implicating the mARS as both a sensor and regulator of the immune response to viral infection 68,69 . Canonically, the mARS complex is reported to possess only 8 of the 19 known mammalian aminoacyl‐tRNA synthetase isoforms (glutamyl‐prolyl, isoleucyl, leucyl, glutaminyl, methionyl, lysyl, arginyl, and aspartyl) 40,64,65,68 which, if true under all homeostatic conditions, could limit its utility as a sensor capable of discerning amino acid homology between epitopes not possessing one or more of the cognate amino acid residues.…”
Section: Resultsmentioning
confidence: 99%
“…101 Meanwhile, adoptive transfer of KRS-treated DCs could effectively induce the polarization of Th1 cells and inhibit tumour growth in mice, indicating that KRS enhanced DC-mediated Th1 cell responses. Lysyl-tRNA synthetase (KRS) induced the maturation of DCs and promoted the production of IL-12 in DCs by regulating the MAPK and NF-κB pathways.…”
Section: Aarss and Immune Responsesmentioning
confidence: 99%
“…Lysyl-tRNA synthetase (KRS) induced the maturation of DCs and promoted the production of IL-12 in DCs by regulating the MAPK and NF-κB pathways. 101 Meanwhile, adoptive transfer of KRS-treated DCs could effectively induce the polarization of Th1 cells and inhibit tumour growth in mice, indicating that KRS enhanced DC-mediated Th1 cell responses. Hildebrand et al found that an Hsa-miR-99b/let-7e/miR-125a cluster could stabilize signal transducer and activator of transcription 3 (STAT3) activity and thus modulate the suppressive antigen-presenting cells (APCs) stimulated by pathogen recognition receptor.…”
Section: Aarss and Immune Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the activation of p38 mitogen-activated protein kinase (MAPKs) signal pathways, nuclear factor kappa-light-chainenhancer of activated B cells (NF-kB) signal pathways and signal transducer and activator of transcription 3 (STAT3) signal pathways could promote the production of the proinammatory cytokines. 5 In contrast, the inhibitors of these signal pathways could reduce the production of proinammatory cytokines aforementioned. Accumulative evidence suggested that STAT3 signal pathway played a vital role in the production of proin-ammatory cytokines in NASH.…”
Section: Introductionmentioning
confidence: 99%